Predictors of Low Cardiac Output Syndrome in Infants After Open-Heart Surgery - Zou, Liang; Yu, Di; Wang, Ruonan; Cun, Yueshuang; Li, Yaping; Wang, Qingfeng; Shu, Yaqin; Mo, Xuming (Frontiers in Pediatrics, 2022)
Objective To evaluate the predictors of low cardiac output syndrome (LCOS) in infants with congenital heart disease (CHD) after cardiopulmonary bypass (CPB). Study design A total of 217 infants were enrolled and classified according to whether they developed LCOS after cardiac surgery. Each infant’s preoperative and intraoperative clinical variables were collected. Results The incidence of LCOS was 28.11% in our study. The univariate analysis showed that the LCOS group was younger than the non-LCOS group (25.69±25.01 days vs. 44.45±26.97 days, P<0.001), with a higher proportion of neonates (60.7% vs. 27.6%, P<0.001) and a higher proportion of patients with a RACHS-1 score ≥4 (50.8% vs. 17.9%, P<0.001). A lower weight (3.70±0.74 kg vs. 4.23±1.10 kg, P=0.001), longer ACC time (61.96 min±21.44 min vs. 41.06 min±18.37 min, P<0.001) and longer CPB time (131.54 min±67.21 min vs. 95.78 min±62.67 min, P<0.001) were found in the LCOS group. The levels of free triiodothyronine (FT3) (4.55±1.29 pmol/L vs. 5.18±1.42 pmol/L, P=0.003) and total triiodothyronine (TT3) (1.80±0.56 nmol/L vs. 1.98±0.54 nmol/L, P=0.026) were also lower in the LCOS group. The multivariate binary logistic regression analysis and receiver operating characteristic (ROC) indicated that the ACC time, FT3 level and body weight were independent predictors of LCOS. Conclusions In our patient population, we first propose that preoperative FT3 can predict the occurrence of postoperative LCOS. ACC time, FT3 level and body weight are independent predictors of LCOS and maybe helpful in reducing the incidence of postoperative LCOS in the future.